Alport syndrome - Karki, P; Shrestha, JK (Nepalese Journal of Ophthalmology, 2010)
Alport syndrome is an oculo-renal syndrome characterized by a triad of clinical findings consisting of hemorrhagic nephritis, sensorineural hearing loss and characteristic ocular findings. We report a young male patient who presented with painless diminution of vision associated with hearing loss. The importance of ophthalmic evaluation for suspecting the disease is highlighted. Keywords: Alport syndrome; sensorineural hearing loss; micro-hematuria; oculo-renal syndrome DOI: 10.3126/nepjoph.v1i2.3690 Nep J Oph 2009;1(2):139-140